Pengaruh Konseling terhadap Kepatuhan pada Pasien Diabetes Melitus Tipe 2 di Poliklinik Penyakit Dalam Rumah Sakit Umum dr. Ferdinand Lumbantobing Sibolga - Panjaitan , Riza Zul Syahri; Nasif , Hansen; Sari , Yelly Octavia (Journal of Pharmaceutical and Sciences, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is a global health threat with a steadily increasing prevalence. Its treatment is lifelong and requires optimal patient adherence to achieve therapeutic success. Pharmacist counseling is one of the interventions believed to improve such adherence. Objective: This study aimed to analyze the effect of pharmacist counseling and patient characteristics (age, gender, education, occupation, and access to hospital care) on medication adherence among T2DM patients. Methods: This study employed a one-group pretest-posttest design conducted at the Internal Medicine Polyclinic of dr. Ferdinand Lumbantobing Regional Hospital, Sibolga. A total of 75 respondents meeting the inclusion criteria were recruited. Adherence was measured using the MARS-10 (Medication Adherence Rating Scale 10 items) questionnaire before and after the counseling intervention. The Mann-Whitney and Kruskal-Wallis tests were used to analyze the influence of patient characteristics, while the Wilcoxon test was used to analyze the effect of counseling. Results: Analysis of demographic variables such as age, gender, education, occupation, and hospital access showed no significant relationship with adherence either before or after counseling (p>0.05). However, pharmacist counseling was proven to significantly improve adherence. The mean adherence score increased from 6.49 (pretest) to 8.08 (posttest) (p<0.05). The proportion of adherent patients rose from 52% to 94.67% following counseling. Conclusion: Patient characteristics had no significant effect on adherence. Pharmacist counseling was shown to be effective in significantly improving medication adherence among Type 2 Diabetes Mellitus patients.